RANCANGAN MULTIMEDIA PEMBELAJARAN BERBASIS TUTORIAL DENGAN SOFTWARE AUTOPLAY MEDIA STUDIO 7.0 - Hasdar Hanafi (Jurnal TAM (Technology Acceptance Model), 2017)
The research is the development of research aims to understand the process of development , conceptual model , physical model of teaching materials electronics skills and effectiveness of teaching materials using program autoplay 7.0 which focus to develop media learning the youth group village Bontopannu Pangkep district . Model of development that is used in this research is a model of the development of ADDIE was done with several tranches is 1). analysis , 2).the design , 3).the development , 4) implementation , 5) evaluation .Learning that media developed , have been validated by two experts by experience that the revision of being used .The trial conducted as many as three times is the trial of individuals , the trial of a group of small and expanded pilot .The results of the analysis response educator shows that learning in the media category of very good .So that it can be concluded that the media learning the result of developing has been responded by a coach or friend peers .The result showed that learning uses the media autoplay 7.0 in engineering maintenance and repair of the telecommunications equipment expressed valid , practical and effective really mature use their experiences in the village Bontopannu Kabupaten Pangkep .The results of a sheet of expert validation of materials with the total value of the average 3.5 be in categories valid and the results of validation media experts with a total value the average 3.23 is at categories valid .Of the results of the analysis response coach and participants training in categories very good , so that expressed the practical use in their experiences .The results of the analysis data the activity of the participants and the participants are categorized as very good , so that it can be declared effective in their experiences.